Robot-assisted supratrigonal cystectomy and augmentation cystoplasty for adult neurogenic lower urinary tract dysfunction: comparison of extracorporeal versus intracorporeal diversion - Sihra, Neha; Lecoanet, Pierre; Dubois, Alexandre; Penafiel, Juan; Haudebert, Camille; Mazeaud, Charles; Mellouki, Adil; Hascoet, Juliette; Ahallal, Younes; Manunta, Andrea; Bentellis, Imad; Peyronnet, Benoit (Therapeutic advances in urology, 2025)
We aim to explore the feasibility of robot-assisted supratrigonal cystectomy and augmentation cystoplasty (RA-SCAC) for the management of adult neurogenic lower urinary tract dysfunction and to compare the functional and surgical outcomes of an intracorporeal and extracorporeal approach. A retrospective review of all patients who underwent robot-assisted supratrigonal cystectomy and augmentation cystoplasty was performed. Data was collected on age, body mass index, American Society of Anaesthesiologists (ASA) score, type and duration of neurological disease, previous abdominal surgery and renal function. Bladder diary, urodynamics and validated symptom score results were recorded at baseline and repeated postoperatively. Intraoperative details included type of diversion, concomitant surgery, duration of surgery, blood loss and conversion to open. Postoperative surgical recovery was also reviewed. The primary endpoint was the rate of major postoperative complications defined as any complication Clavien-Dindo grade ≥3 occurring within the first 90 days postoperatively. There were 26 patients in total; 7 performed extracorporeally and 19 intracorporeally. Mean age was 41.5, mean BMI 24.4 and majority were ASA score 2 (61.5%). Twelve (46.1%) patients had spinal cord injury and 6 (23.1%) spina bifida. Seven (26.9%) had a concomitant procedure including bladder neck artificial urinary sphincter (AUS) insertion, bladder neck fascial sling or creation of a continent catheterisable channel. The surgical outcomes were analysed separately for those that had RA-SCAC only versus RA-SCAC with a concomitant procedure. The operative time was shorter in the intracorporeal group, and the length of stay was similar in both groups. The total number of major postoperative complications was low (n = 3; 11.5%). All urodynamic parameters significantly improved at 6 months in the intracorporeal group. Median number of urinary incontinence episodes per 24 h decreased significantly in both groups at 3 months but the continence status and ICIQ-UI SF demonstrated statistical significance in the intracorporeal group only. In conclusion, robot-assisted supratrigonal cystectomy and augmentation cystoplasty is feasible in adult neurological patients, favouring an intracorporeal approach. Robot-assisted supratrigonal cystectomy and augmentation cystoplasty for adult neurogenic lower urinary tract dysfunction and a comparison of different surgical techniques Neurological disease in the adult population can cause lower urinary tract dysfunction and may require surgical intervention when less invasive treatments have failed. Augmentation cystoplasty has traditionally been performed as an open operation and can be associated with significant peri-operative morbidity due to its surgical complexity. We reviewed the records of 26 patients who underwent this operation using a minimally invasive robot-assisted approach. We compared two different surgical techniques (intracorporeal versus extracorporeal diversion) and looked at both the functional and surgical outcomes to assess its feasibility in this patient group. Our findings suggest that a robot-assisted approach is safe and feasible and that when performed, an intracorporeal diversion is preferential.